Internet of Things International Workshop, IOT 2012, Changsha, China, August 17-19, 2012. Proceedings - Wang, Yongheng; Zhang, Xiaoming (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the International Workshop on Internet of Things, IOT 2012, held in Changsha, China, during August 17-19. The 95 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on wireless sensor networks; RFID; sensors and equipments; data processing; security; applications and others.